Effect Of Oxytocin Massage On Milk Production In Pospartum Mothers Post SC 2 At Sawerigading Hospital Palopo - Nurhasanah; Warlindah; Helmi Nince Bernadus Coebraad (Jurnal Life Birth, 2022)
Newborns need optimal care from birth, one of which is the ideal food. Newborn babies do not need other intakes other than breast milk from their mothers. But in reality, exclusive breastfeeding is not as easy as imagined. Various obstacles can arise to providing exclusive breastfeeding for the first six months of a baby's life. o, determine the effect of oxytocin massage on breast milk production in postpartum mothers at Sawerigading Palopo Hospital in 2021". Research Design: The type of research used in this study is a quasi-experimental research design with an Equivalent grub, pretest-posttest design. The population is the whole of objects or individuals who have certain characteristics (traits) to be studied. The population is also called the universe (universe), which means the whole can be either living or animate objects. The population in this study were all postpartum mothers, as many as 40 people. The sample in this study was 40 postpartum mothers. total sampling is the entire population is sampled. Based on the results of the study, it was found that the administration of oxytocin massage in the intervention group had a significant effect on increasing breast milk production. Oxytocin massage was applied to the mother during the puerperium, where the p-Value = .000 was smaller than the value of (0.05).